2019
DOI: 10.1080/13607863.2019.1597012
|View full text |Cite
|
Sign up to set email alerts
|

Depressivity and mortality risk in a cohort of elderly men. A role of cognitive and vascular ill-health, and social participation

Abstract: Objectives: Depressive symptoms in the elderly have been shown to be associated with increased mortality. The purpose of this study was to examine symptoms of depression in octogenarian men and their association with all-cause mortality, and whether physical, cognitive and social factors influence this association. Methods: Out of the 703 initially included 55-years-old men, from the prospective cohort study "Men born in 1914", we studied 163 survivors who could take a part in a survey at age 81, and followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
1
2
0
1
Order By: Relevance
“…In our results, social participation was also associated with a decreased risk of mortality in men. Our results and previous findings on the association between depression and increased risk of mortality [ 26 , 27 ] have suggested that social participation contributed to a decreased risk of mortality in Japanese men who were more likely to experience a retirement event in their 60s. For women, there was no association between changes in frequency of social participation and a decreased risk of mortality.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In our results, social participation was also associated with a decreased risk of mortality in men. Our results and previous findings on the association between depression and increased risk of mortality [ 26 , 27 ] have suggested that social participation contributed to a decreased risk of mortality in Japanese men who were more likely to experience a retirement event in their 60s. For women, there was no association between changes in frequency of social participation and a decreased risk of mortality.…”
Section: Discussionsupporting
confidence: 81%
“…A report which examined the relationship between the changes in social capital and depression observed that changes in social capital were important in the prevention of depression [ 24 ]. Based on these reports and findings that self-related health and depressive symptoms increased the risk of mortality [ 25 , 26 , 27 ], continued social participation may prevent depressive symptoms and other health problems, maintain health, and provide a protective effect against mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms of anxiety and of depression (hereafter also referred to as psychological distress) are common in older adults 5 and have been associated with greater morbidity 6,7 and mortality, 8,9 and poor quality of life 10 . With the exponential ageing of the world population, 11 psychological well‐being in late life is set to become a major public health issue.…”
Section: Introductionmentioning
confidence: 99%
“…A presença da sintomatologia depressiva traz consequências como aumento da incidência de doenças cardiovasculares (7,8), doença coronariana, insuficiência cardíaca, acidente vascular cerebral (9), maior risco de complicações dialíticas e redução da qualidade de vida (8). Outro desfecho associado à sintomatologia depressiva que vem ganhando destaque é o aumento do risco de mortalidade (7,(10)(11)(12)(13)(14)(15)(16). O melhor entendimento dessa associação é de interesse da saúde pública, pois pode apoiar estratégias que visem à promoção da saúde da pessoa idosa, diminuir potenciais impactos nos sistemas de saúde e previdenciário e guiar a implementação de estratégias de controle e prevenção da sintomatologia depressiva (8).…”
unclassified